2021
DOI: 10.1038/s41589-020-00699-x
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up de novo design of functional proteins with complex structural features

Abstract: De novo protein design has enabled the creation of novel protein structures. To design novel functional proteins, state-of-the-art approaches use natural proteins or first design protein scaffolds that subsequently serve as templates for the transplantation of functional motifs. In these approaches, the templates are function-agnostic and motifs have been limited to those with regular secondary structure. Here, we present a bottom-up approach to build de novo proteins tailored to structurally complex functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 61 publications
0
76
0
Order By: Relevance
“…The major challenge was developing a method to bioengineer a multiepitope coding sequence that would result in a protein [ 39 , 40 ]. To maintain the interactions of the epitopes with antibodies, it was clear that the approach needed to maintain their sequences on the surface of the resulting protein.…”
Section: Discussionmentioning
confidence: 99%
“…The major challenge was developing a method to bioengineer a multiepitope coding sequence that would result in a protein [ 39 , 40 ]. To maintain the interactions of the epitopes with antibodies, it was clear that the approach needed to maintain their sequences on the surface of the resulting protein.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of surface similarity clearly increases sequence recovery rates relative to other scoring schemes. This approach can be readily applied for the design of experimental combinatorial libraries to reduce library sizes, as the high sequence recovery rates suggest that surface-centric design is especially interesting to design novel proteins that mimic surface patches of other proteins, as it is the case for the design of novel immunogens for vaccine development (36)(37)(38). We demonstrated that surface-centric design could be used to generate targeted libraries to optimize binding specificity of a previously reported IL-2 design (61).…”
Section: Discussionmentioning
confidence: 96%
“…By focusing on protein interfaces, the correct sequence does not solely depend on minimizing the Rosetta scoring function, but rather needs to represent the surface properties of the interface site. While such design scenario has limited applicability for the de novo design of protein-protein interactions, it is important for applications in the domain of immunogen design for vaccine development where the surface mimicry of known surfaces (neutralizing epitopes) is critical for the biological activity of this type of design (34,(36)(37)(38). In this benchmark we considered nine protein-protein complexes, grouped into three categories (low complementarity, high complementarity, antibody/antigen), and evaluated the performance by assessing sequence recovery (Fig.…”
Section: Protein Interface Sequence Recoverymentioning
confidence: 99%
See 2 more Smart Citations